Determinants of Parcel Locker Adoption in Last-Mile Delivery with Emphasis on Logistics Value, Consumer Orientation, Value Co-Creation, and Green Awareness - Lis Lesmini; Prasadja Ricardianto; Nofrisel; Yana Tatiana; Edi Abdurachman (Politeknik APP Jakarta, 2026)
This study aims to identify the key factors that influence consumers' intention to adopt parcel locker services in last-mile delivery, using Service-Dominant Logic to explain how value is created between consumers and service providers. The research was conducted in Jakarta using a quantitative approach. Data were collected from 412 e-commerce users through a structured survey using stratified random sampling across five administrative cities. The Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with appropriate statistical software. The study concludes that consumer adoption of parcel lockers depends more on collaborative experiences and personalized interactions than on environmental concerns. Value Co-Creation plays a central role as the main pathway driving adoption.